Socioeconomic inequalities in the use of dental health care among the adult population in Serbia - Corovic, Snezana; Janicijevic, Katarina; Radovanovic, Snezana; Vukomanovic, Ivana Simic; Mihaljevic, Olgica; Djordjevic, Jelena; Djordjic, Milan; Stajic, Dalibor; Djordjevic, Ognjen; Djordjevic, Gordana; Radovanovic, Jovana; Selakovic, Viktor; et al. (Frontiers in Public Health, 2023)
Objectives The aim of this paper is to assess the association of demografic and socioeconomic determinants with utilization of dental services among Serbian adults. Materials and methods The study is a part of the population health research of Serbia, conducted in the period from October to December 2019 by the Institute of Statistics of the Republic of Serbia in cooperation with the Institute of Public Health of Serbia “Dr. Milan JovanovićBatut” and the Ministry of Health of the Republic of Serbia. The research was conducted as a descriptive, cross-sectional analytical study on a representative sample of the population of Serbia. For the purposes of this study, data on the adult population aged 20 years and older were used. Results Men were approximately 1.8 times more likely than women to not utilize dental healthcare services (OR = 1.81). The likelihood of not utilizing dental healthcare protection rises with increasing age, reaching its peak within the 65–74 age range (OR = 0.441), after which it declines. Individuals who have experienced marital dissolution due to divorce or the death of a spouse exhibit a higher probability of not utilizing health protection (OR = 1.868). As the level of education and wealth diminishes, the probability of abstaining from health protection increases by 5.8 times among respondents with an elementary school education (OR = 5.852) and 1.7 times among the most economically disadvantaged respondents (OR = 1.745). Regarding inactivity, respondents who are not employed have a 2.6-fold higher likelihood of not utilizing oral health care compared to employed respondents (OR = 2.610). Conclusion The results suggest that individual sociodemographic factors influence utilization of dental services by Serbian adults and confirmed the existence of socioeconomic disparities.